GRAZAX®: a sublingual immunotherapy vaccine for Hay fever treatment: from concept to commercialization. Issue 12 (2nd December 2019) - Barber, Domingo; Rico, Pilar; Blanco, Carlos; Fernandez-Rivas, Montserrat; Ibañez, Maria Dolores; Escribese, Maria M.
ABSTRACT: Allergen immunotherapy has been used for more than 100 y, but only recently underlying immunological mechanisms have started to be understood. New Allergy vaccines are now considered to be full pharmaceutical products, that should comply with general as well as specific pharmaceutical legal framework. GRAZAX® is the first global allergy vaccine developed in compliance with the new legal environment and is thus a reference for developing new allergy vaccines. Here, we provide a rationale description of GRAZAX®, providing a sequential description of its pharmaceutical and clinical development. With more than 25 clinical trials, involving more than 8000 patients, including as well three 5-y prospective clinical trials, GRAZAX® is a key product to understand the unique position of allergen-specific immunotherapy as a disease-modifying intervention.